The Literary Techniques in Political Poetry: A Case Study from the Column “Kawee Kraward” in Matichonweekly Online in the Year B.E. 2559 - 2564 - Ngamrungrot, Nopphawan (Journal of Humanities and Social Sciences Suratthani Rajabhat University, 2023)
This research article aimed to study the literary techniques in political poetry from the column "Kawee Kraward" in Matichonweekly Online in the year B.E. 2559-2564. This qualitative research collected literary data on the type of poetry in the column "Kawee Kraward" in Matichonweekly Online, selecting to study only the poetry with a political concept or those reflecting political events in the years B.E. 2559–2564. Thus, using literary techniques as a research framework, 36 poems were selected. The study illustrated that poets used literary techniques such as diction consisting of experiential verbs and behavioral verbs, allusion consisting of allusion to phrase or allusion to other literature, allusion to individuals and speech, simile, metaphor, metonymy, and symbolism. These techniques act as a tool to convey emotions, depression, and the poet's opinions on political events based on value determination and to negatively criticize government administrations that use their power to limit the rights and freedoms of the people. Literary techniques are essential in creating a new poem by changing political contexts.